An ovarian mucinous cystadenoma with adnexal tuberculosis: a case report - Panchonia, Ashok; Kulkarni, Chandrahas V.; Mehar, Rakesh; Malpani, Garima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
We report the occurrence of a case of a benign ovarian tumour- mucinous cystadenoma ovary with adnexal tuberculosis. Our case was a middle-aged Indian woman who presented with abdominal distension and discomfort at the gynaecology clinic of M.Y. hospital, Indore. The data were collected by history-taking, clinical examination, laboratory investigations, transabdominal ultrasonographic examination, and by histopathological study of the excised surgical specimen. It was reported as ovarian mucinous cystadenoma with adnexal TB. This case report emphasizes the significance of thorough evaluation of all women presenting with vague abdominal pains and thorough search of any other pathology in the specimen, like in our case it was tuberculosis. With the increasing awareness of such conditions, more and more cases could be detected and reported.